An analysis of teacher-pupil interaction in a Grade V class of children with behavior problems - Castañeda, Elynor E. 1938-; Adorio, Mercedes P. (Quezon City College of Education, University of the Philippines Diliman, 1977)
The purpose of this study was to present an analysis of the teacher-pupil behavior pattern of verbal interaction as observed and recorded in a Grade Five Class of Children with Behavior Problems in Taytay Elementary School in the Division of Rizal. Fladers Interaction Analysis Categories was used in the observation and analysis of verbal interaction procedures. It was found that verbal interaction in a class of children with behavior problem was teacher rather than pupil dominated. Pupil initiated talk was very much less than pupil responses and their initiated talk was generally to other pupils. The teachers' verbal behavior may be described as mostly teacher initiated talk and less of teacher responses.
Vita.
Thesis (Master of Arts in Teaching Special Education - Children with Behavior Problems)--University of the Philippines, Diliman
Keywords: Interaction analysis in education -- Philippines -- Taytay (Rizal); Children with mental disabilities -- Education (Elementary) -- Philippines -- Taytay (Rizal); Special education -- Philippines -- Taytay (Rizal); Behavior disorders in children -- Philippines -- Taytay (Rizal)